Small Group Learning - Gary Loyd (Association of American Medical Colleges, 2014)
Abstract This module is a resource on how to plan and implement small-group teaching sessions to educate residents and medical students. The minimum target level of Bloom's Taxonomy is at the application level, with the possibility of raising it to synthesis. Thus, participating faculty members should be able to acquire enough knowledge, skill, and attitude from this module to successfully implement small-group teaching at their own institutions. This session was first used at the 2009 Society for Education in Anesthesia's Workshop on Teaching. It was repeated in 2010, 2011, and 2012. Participant feedback gave the session high marks for content and improvement in knowledge, skills, and attitude. Participants also indicated they planned to implement small-group teaching sessions at their own institutions.